Protein Energy Malnutrition in Liver Cirrhosis - Achmad Fauzi; Unggul Budihusodo; Marcellus Simadibrata; Abdul Aziz Rani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Protein-energy malnutrition is common in patients with liver cirrhosis, especially in advanced and severe stage. Liver cirrhosis patients with malnutrition have increasing risk to get post-operative complication and mortality. The etiology of malnutrition is multifactorial. Substrate metabolism in liver cirrhosis is characterized by insulin resistance, influencing the transport and elimination of nonoxidative glucose by muscle. Protein turnover occurs in normal rate or it may increase with the increasing of protein degradation. Oxidation and metabolic clearance of fat are normal in patients with liver cirrhosis. Most clinicians used to feed patients with liver disease with a common sense approach, otherwise many investigators suggest the use of nutritional supplements and specialized formulations aggressively, in older to correct pre-existing protein-calorie malnutrition and to stimulate hepatic regeneration. Keywords: malnutrition, liver cirrhosis, branched-chain amino acid